Effect of black plastic mulch and raised bed on soil temperature and yield of sweet pepper - Locher, J.; Ombódi, A.; Kassai, T.; Tornyai, T.; Dimény, J. (International Journal of Horticultural Science, 2003)
A field study was conducted in Central Hungary in 2001 and 2002 in order to evaluate the effects of black plastic mulch and raised bed on soil temperature and on yield and fruit quality of sweet pepper (Capsicum annuum L. cv. `Kárpia’). The experiment was a complete block design with four replicates. Four different technologies were used as treatments: raised bed with black PE mulch, raised bed without mulch, level ground with black PE mulch and level ground without mulch. In both years soil temperature was the highest in the covered raised bed treatment, about 2 °C higher than in the uncovered raised bed. Optimum soil temperature requirement of sweet pepper roots was met to the highest degree in case of the covered raised bed, 26-28% of the total growing period. The more favourable soil temperature conditions resulted in better yield, compared to the uncovered level ground treatment the covered raised bed treatment produced 19% and 14% higher yield in 2001 and 2002, respectively.